Research Ethics - Dibsono, Dibsono (Forum Manajemen; Vol 12 No 66 (1998): Forum Manajemen Prasetiya Mulya | Back to Basics, 1998)
To avoid the misuse of the data, the research must make sure that access to the data is limited as well as keeping the anonymity of the individual respondents .